The use of information communication technology by A-level teachers in selected secondary schools in Gweru, Zimbabwe - Gocha, Munyaradzi; Musungwini, Samuel; Chitanana, Lockias (International Journal Pushing House, 2019)
The purpose of this study was to investigate how A-level teachers in selected Gweru urban schools were using ICT in their teaching. The objectives of the study were: To establish computer hardware and software resources that were available in high schools in Gweru urban that offer Advanced level classes and how are they being used? To determine the extent of teacher readiness among Advanced level teachers in using the available resources in Gweru urban high schools? To determine the perceptions of Advanced level teachers on the role of ICT in teaching and learning in Gweru urban? Results show that Government schools were not well resourced in terms of ICT hardware equipment as well as software irrespective of location while the private school was better resourced. Advanced level teachers in Gweru urban are generally not ready to use the available ICT resources beyond the most basic applications. All sampled teachers believed that computers and other ICT equipment were important in teaching regardless of school status.